MODERN CONTRACTS, IMAGE TRANSFER AND CAUSA – ANALYSIS OF SPONSORSHIP AGREEMENT - Stanojević, Petra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The paper focuses on specific kinds of contracts conducted with marketing purpose in mind – image transfer. The main objective is to shed light on this question and its significance in the context of social media content expansion and lack of theoretical disscusions on this topic. The thesis of the paper suggests that all relationships to be analysed are actually the same type of agreement – sponsorship agreement. Therefore the paper serves as a thorough analysis of its characteristics, in relation to how it interacts with existing norms. Suggestions on how this contract should be regulated will be made towards the conclusion. The importance of discussing this topic consists in lack of regulation and theoretical works as well as its frequency and legal uncertainty in case of dispute.
Keywords: Sponsorship. - Image transfer. - Advertising. – Contracts.